2007
DOI: 10.1002/pola.21996
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic polyamine architectures with lipophilic shells as nanocompartments for polar guest molecules: A comparative study of their transport behavior

Abstract: Dendritic core‐shell architectures were synthesized by simple melt reactions of polyethylenimine (PEI) with different fatty acids. These systems were investigated towards their ability to encapsulate various guest molecules. Parameters, such as the length of the attached alkyl chain, size of the polymer core, concentration of the core‐shell architecture in solution, pH, and nature of the guest molecule were investigated and compared. Guest molecules that bear anionic groups, such as carboxylate, phosphate, sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 39 publications
(67 reference statements)
2
55
0
Order By: Relevance
“…We have also reported on a similar aggregates formation among stable core-shell architectures. [10,11] However, the critical aggregation concentrations (CACs) are strongly dependent on the length of PEG shells. For the N1 system which has a PEG chain with 4 EG units, a CAC of 4.0 Â 10 À5 M was obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also reported on a similar aggregates formation among stable core-shell architectures. [10,11] However, the critical aggregation concentrations (CACs) are strongly dependent on the length of PEG shells. For the N1 system which has a PEG chain with 4 EG units, a CAC of 4.0 Â 10 À5 M was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…During the last decade, the dendritic core-shell architectures have been considered as unimolecular systems during the encapsulation of guest molecules. [10][11][12][13] In the past, we have observed that shell functionalized hyperbranched polyamines can also encapsulate polar guest molecules and transport them to a nonpolar organic media, such as chloroform from aqueous media. [8,9] Further research confirmed that the formation of aggregates among dendritic core-shell architectures played a predominant role in the encapsulation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In recent years, a variety of polymeric materials have been developed and tested with plant oils as feedstocks. Among other products, plant oil-based polyurethanes (PUs) are the most extensively studied attributing to their simple preparation yet greatly promising applications.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] This property is related to the roughly defined structure of the hyperbranched core. On the other hand, highly specific molecular recognition is realized almost exclusively by a specific host/guest interactions such as hydrogen bonding, metal/ligand interaction, topological trapping, or their appropriate combinations.…”
Section: Introductionmentioning
confidence: 99%